2019
DOI: 10.1007/s13592-019-00679-8
|View full text |Cite
|
Sign up to set email alerts
|

Methods for rearing ground-nesting bees under laboratory conditions

Abstract: Ground-nesting bees are largely undervalued, both in terms of their use as model species for behavioural studies, and in terms of their agricultural benefit as pollinators in crop systems. But, why? One potential barrier limiting their use as model species may be our understanding of how to effectively establish and maintain groundnesting bees in the laboratory. Here we review how artificial nests are used to study ground-nesting bees and provide guidelines for building, starting and maintaining artificial nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 88 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…(Cucurbitaceae), and have, therefore, been reared in cages or greenhouses to investigate the effects of agricultural practices on ground‐nesting bees. A few species of ground‐nesting bees have even been reared in the laboratory (reviewed in Leonard and Harmon‐Threatt 2019), using observation chambers with glass windows to investigate their behaviour and nest architecture (Michener et al ., 1955). These nest boxes, similar to the ones commonly used to study ants, kept below‐ground or moved above‐ground, have been used to observe Lasioglossum zephyrum (Smith) (Batra, 1964, 1968; Michener & Brothers, 1971), Nomia melanderi (Batra, 1970), Macrotera portalis (Timberlake) (Danforth, 1991) and Anthophora sp.…”
Section: Methods For Studying the Nesting Habitat Of Ground‐nesting Beesmentioning
confidence: 99%
See 3 more Smart Citations
“…(Cucurbitaceae), and have, therefore, been reared in cages or greenhouses to investigate the effects of agricultural practices on ground‐nesting bees. A few species of ground‐nesting bees have even been reared in the laboratory (reviewed in Leonard and Harmon‐Threatt 2019), using observation chambers with glass windows to investigate their behaviour and nest architecture (Michener et al ., 1955). These nest boxes, similar to the ones commonly used to study ants, kept below‐ground or moved above‐ground, have been used to observe Lasioglossum zephyrum (Smith) (Batra, 1964, 1968; Michener & Brothers, 1971), Nomia melanderi (Batra, 1970), Macrotera portalis (Timberlake) (Danforth, 1991) and Anthophora sp.…”
Section: Methods For Studying the Nesting Habitat Of Ground‐nesting Beesmentioning
confidence: 99%
“…Alkali bees (Nomia melanderi Cockerell), which are sometimes managed for alfalfa pollination, are known for nesting in clay soils with a pH > 8 and a high moisture level (Cane, 2003(Cane, , 2008Vinchesi et al, 2013). Fortel et al (2016) found no influence of soil texture on species richness or abundance of ground-nesting bees in experimental plots set up for this purpose; however, this result could mask interspecific differences, since species likely differ in their soil-texture preferences (Leonard & Harmon-Threatt, 2019). Seemingly contradictory results could also be due to the use of different methods for soil textural analysis, from sieving and weighing different soil fractions, to particle size analysis either with a hydrometer (Bouyoucos method) or a pipette (U.S. Department of Agriculture, Bureau of Plant Industry, Soils, 1951).…”
Section: Abiotic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not seem necessarily due to rarity, as the species is distributed across 24 counties in Minnesota in the University of Minnesota insect collection (as of September 2019). Development of variations in "nest trap" designs (e.g., Sheffield et al, 2015) and rearing methods (e.g., Graham et al, 2015;Leonard & Harmon-Threatt, 2019) may lead to alternate nest trapping methods for bees with atypical nesting substrate use, such as A. terminalis.…”
Section: Discussionmentioning
confidence: 99%